Erratum: Pushkareva, I., et al. The Influence of Vanadium Additions on Isothermally Formed Bainite Microstructures in Medium Carbon Steels Containing Retained Austenite. Metals 2020, 10, 392 - Irina Pushkareva; Babak Shalchi-Amirkhiz; Sébastien Yves Pierre Allain; Guillaume Geandier; Fateh Fazeli; Matthew Sztanko; Colin Scott (Metals, 2020)
The authors wish to make the following erratum to this paper [...]